2021
DOI: 10.1007/s11252-021-01147-x
|View full text |Cite
|
Sign up to set email alerts
|

The queen of the island: On the density and distribution of the Eurasian Collared-Dove (Streptopelia decaocto) in Cozumel

Abstract: The Eurasian Collared-Dove (Streptopelia decaocto) is one of the most successful invasive bird species across the world. Worryingly, the invasive dove is a known reservoir of many diseases, some of which can potentially infect mammals (including human beings). Additionally, aggressive behaviors have been recorded toward other bird species resulting in territory and nest usurpation. Thus, the presence of this species poses an important risk for native species with similar habits, particularly in insular systems… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…The inverse distance weighting (IDW) method was then used in QGIS, which corresponds to a deterministic spatial interpolation that assumes that the closest sites are more similar than those that are further away [36]. This method was used to visualize patterns of richness and abundance in both plants and animals [37][38][39]. With this interpolation method, it was possible to control the importance of known sites on the interpolated values (power (p)), as well as sites that can influence the interpolation (neighborhood (n)).…”
Section: Discussionmentioning
confidence: 99%
“…The inverse distance weighting (IDW) method was then used in QGIS, which corresponds to a deterministic spatial interpolation that assumes that the closest sites are more similar than those that are further away [36]. This method was used to visualize patterns of richness and abundance in both plants and animals [37][38][39]. With this interpolation method, it was possible to control the importance of known sites on the interpolated values (power (p)), as well as sites that can influence the interpolation (neighborhood (n)).…”
Section: Discussionmentioning
confidence: 99%
“…Later, the same authors explored the effects of this Asian invasive species on plant community structure and composition [10]. Similarly, García-Arroyo et al [11] found that the Eurasian collared-dove (Streptopelia decaocto (Frivaldszky, 1838)), one of the most successive birds worldwide, was very abundant in the urban areas of the island. Additional alien invasive species reported in Cozumel include the lionfish (Pterois volitans (Linnaeus, 1957)) [12]; a tarantula (Brachypelma vagans (Ausserer, 1875)) [13]; and the boa (Boa imperator (Daudin, 1803)) [14].…”
Section: Introductionmentioning
confidence: 98%
“…The Cozumel Curassow is also threatened by the introduction of non-native predators, as it may have evolved in the absence of predators (Martínez-Morales and Cuarón 1999; Romero-Najera 2004; Valenzuela-Galván et al 2022). Exotic species have increased in concordance with the growth of the local human population (Morales-Contreras et al 2020; García-Arroyo et al 2021), which in the last 20 years has increased by at least 70% (INEGI 2015). This is in addition to the 4 to 5 million tourists that Cozumel receives annually (Palafox-Muñoz and Collantes-Chávez 2009).…”
Section: Introductionmentioning
confidence: 99%